Some Morphological Changes in the Structure of the Heart (Eurasian Medical Research Periodical, 2023)
The aim of our work is to identify features of morphogenesis in postnatal development, the study of the histological structure of different departments and membranes of rat heart at 1-22 days after birth. The object of the study was the heart of the 50 rats at 1, 6, 11, 16, 22 days after birth. Notes alternating periods of acceleration and deceleration of the growth rate increasing thickness of the atria and ventricles. Endocardial and epicardial thickness increases significantly less. The growth rate of the thickness of the ventricular myocardium were observed in rats 6 and 16 days of age. Structural changes occur due to the growth of the organism. Feature of the structure and topography of microvessels heart is their distribution in the course of cardiomyocytes and the relationship with fibrous connective tissue structures of cardiomyocytes.